Early dinner reduces nocturnal gastric acidity. Issue 8 (August 1989) - Duroux, P; Bauerfeind, P; Emde, C; Koelz, H R; Blum, A L
Abstract : This study examines whether eating food at different times has differential effects on intragastric pH. Experiments were done in 23 healthy volunteers (12 men). Intragastric acidity was monitored by ambulatory 22 hour pH-metry. Composition of meals was standardised: breakfast and lunch at 7 am and 12 noon respectively, and dinner at 6 or 9 pm, in random order. The time of going to bed and getting up was also standardised. With early dinner nocturnal pH was higher, than with late dinner (pH median: 1.67 and 1.39, p less than 0.001). During the remaining time periods, pH values were similar. Thus early dinner may be helpful in conditions where low intragastric acidity is desirable.